Clinical implications of microRNAs in human glioblastoma - Mizoguchi, Masahiro; Guan, Yanlei; Yoshimoto, Koji; Hata, Nobuhiro; Amano, Toshiyuki; Nakamizo, Akira; Sasaki, Tomio (Frontiers in Oncology, 2013)
Glioblastoma (GBM) is one of the most common and dismal brain tumors in adults. Further elucidation of the molecular pathogenesis of GBM is mandatory to improve the overall survival of patients. A novel small non-coding RNA molecule, microRNA (miRNA), appears to represent one of the most attractive target molecules contributing to the pathogenesis of various types of tumors. Recent global analyses have revealed that several miRNAs are clinically implicated in GBM, with some reports indicating the association of miRNA dysregulation with acquired temozolomide (TMZ) resistance. More recent studies have revealed that miRNAs could play a role in cancer stem cell (CSC) properties, contributing to treatment resistance. In addition, greater impact might be expected from miRNA-targeted therapies based on tumor-derived exosomes that contain numerous functional miRNAs, which could be transferred between tumor cells and surrounding structures. Tumor-derived miRNAs are now considered to be a novel molecular mechanism promoting the progression of GBM. Establishment of miRNA-targeted therapies based on miRNA dysregulation of CSCs could provide effective therapeutic strategies for TMZ-resistant GBM. Recent progress has revealed that miRNAs are not only putative biological markers for diagnosis, but also one of the most promising targets for GBM treatment. Herein, we summarize the translational aspects of miRNAs in the diagnosis and treatment of GBM.